(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Cystitis is one of the most common inflammatory diseases of the urinary tract, particularly among women of working age. Timely and accurate diagnosis is crucial for selecting an effective treatment strategy and preventing complications. This article reviews modern diagnostic criteria for cystitis based on clinical presentation and the findings of laboratory and instrumental investigations. Special attention is given to the role of urinalysis, bacteriological examination, determination of pathogen susceptibility to antibacterial agents, as well as the use of ultrasound and endoscopic methods. The application of a comprehensive diagnostic approach improves diagnostic accuracy, shortens treatment duration, and helps prevent chronic progression of the inflammatory process.